PENGARUH PEMAHAMAN INVESTASI DAN KEMAMPUAN FINANSIAL MAHASISWA TERHADAP KEPUTUSAN INVESTASI PADA PASAR MODAL SYARIAH - David Stiven Perdana; Ahmad Hasrul Maulana Kidam; Ana Magfiroh (Program Studi Ekonomi Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
This research aims to determine the influence of financial understanding and ability on Sharia capital market investment decisions of students majoring in Sharia Economics at IAI Ibrahimy Banyuwangi with a sample size of 31 students. The results of this research state that Investment Understanding (X1) has a positive effect on Investment Decisions (Y). This can happen because the calculated t value of 2.436 is greater than the t table value of 2.048 with a significance value of 0.021 which is smaller than 0.05. Financial Capability (X2) has no positive effect on Investment Decisions (Y). It can be seen from the calculated t value of 0.944 which is smaller than the t table value of 2.04841 with a significance value of 0.353 which is greater than 0.05. Investment Understanding (X1) and Financial Capability (X2) jointly influence Investment Decisions (Y). It can be seen that the calculated F value is 9.880 which is greater than the F table 3.35 with a significance value of 0.001 which is smaller than 0.05. Calculation of the Coefficient of Determination (R2) shows a value of 0.372 or 37.2%. This shows that the independent variables in this research, namely Investment Understanding (X1) and Financial Capability (X2), can only explain 37.2% of the dependent variable, namely Investment Decisions (Y), while the remaining 62.8% is explained or influenced by the variable others not included in this study.